The Dark Side of Gravity (Global Journal of Science Frontier Research, 2013)
Adopting a non geometrical point of view, we are led to an alternative theory of the order two and symmetric gravitational tensor field of GR. Considering our spacetime to be flat and non dynamical, this field can no more be interpreted as its metric. The true metric is a globally Minkowskian background, a context which justifies a genuine Rehabilitation of the global discrete spacetime symmetries involved in the structure of the Lorentz group along with their 'problematic' representations: the negative energy And tachyonic ones. It turns out that about this background our gravitational field must appear in two discrete symmetry reversal conjugate forms, different but non independent symmetric order two tensors which must be treated on the same footing in our actions. The discrete symmetry reversal invariant actions, equations and their conjugate solutions are obtained. The conjugate form generates a Dark Side of Gravity. Indeed, matter living there can only interact antigravitationally with matter on our side.We show that stability is granted. In this Dark Gravity theory (DG), the new Schwarzschild solution in vacuum only starts to differ from that of General Relativity at the Post-Post-Newtonian order. DG does not violate WEP and though it violates SEP, the theory passes all present SEP no violation tests except the Pioneer anomalous blue-shift one, an SEP violating effect which is a natural outcome.
Keywords: negative energies; time reversal; tachyons; anti-gravity PACKS : 0450Kd